THE STRATEGY OF ACUTE COMPLICATION PREVENTION: HYPOGLIKEMIA ON NON INDEPENDENT DIABETES MELLITUS - Lale Wisnu Andrayani (Jurnal Kesehatan Prima, 2017)
WHO estimates the number of diabetes mellitus patients in indonesia will rise from 8.4 million in 2000 become 21.3 million by the year 2030 ( PDPERSI , 2011 ) with the biggest populations ( 90 % ) on the non independent diabetes mellitus ( NIDM ) type ( Askandar ,2009 ; Perkeni , 2006 ). Diabetes Mellitus disease need an adequate blood sugar management but an effort of blood sugar control in preventing the complications of  diabetes mellitus can be the beginning of the occurrence of acute and chronic complications which have an impact on the increasing of  morbidity and mortality, for instance a hypoglycemia ( shiciri , 2000; wang , 2012 ). According to Wang (2012) a hypoglycemia is a greatest obstacle in striving for adequate blood sugar control management on NIDM thus it is needed the strategy of acute complication prevention on patients with NIDM to prevent hypoglycemia.  Method: identify literature that relevant in the form of articles and research. Results: 3 from 5 articles was a randomized controlled trial (RCT). There were several trending strategy in hipoglycemia prevention for instance standard of procedure (SOP), counselling, self-monitoring of blood glucose programme ( SMBG), and U-health care. The used of combination several methods including involved the technology on internet based indicated a better results than used one of the method. Conclusion: the use of combination methods in proper hypoglycemia prevention, including telehealth possesses greater advantage in preventing hypoglycemia and its implementation in Indonesia has a great opportunity to be developed.